Computer-aided project management - Suhanic, George (Oxford University Press, 2001)
Ideal for advanced undergraduate- and graduate-level courses in management, project, systems, and construction engineering, Computer-Aided Project Management builds a bridge from the genesis of project management principles through today's software, developing a postmodern project management systems paradigm for the twenty-first century. Adopting a unique systems perspective that emphasizes project coding--an essential skill in project database management--this book shows what fundamental project management principles are, what they do, and how they work in the software environment. Addressing all phases of a project, it illustrates and expands theories through the use of realistic case studies--which are based on actual project experience--and extensive exercises running on PCs. An important feature of systems project management, the use of "scope" and "quality," is also discussed.